2005
DOI: 10.1264/jsme2.20.69
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Mucus Layer on the Surface of the Bluegill (Lepomis macrochirus) and the Bacterial Flora in the Mucus

Abstract: The layer of mucus on the surface of bluegills (Lepomis macrochirus) captured in Lake Biwa was characterized as 1) large enough to host microbes (ca. 76 mm thick), 2) a physically different environment from the surrounding lake water in viscosity and buffering capacity, and 3) chemically rich in organic substances, which may be utilized as nutrients. Based on DAPI staining and on the number of colonies formed respectively, it was found that ca. 10 3 times and 3 to 7 times the number of microbial cells were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…On the other hand, these mucus strains would hardly be able to grow in sufficiently large numbers in the lake water, as described above, so it might be hard for them to maintain a stable population in the lake water. The faster growth-rate constant of mucus strains in the 20-fold diluted mucus and their insufficient growth in the lake water may result in a characteristic bacterial flora in the mucus which is different from that in the lake water, as revealed in our previous study 6) .…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…On the other hand, these mucus strains would hardly be able to grow in sufficiently large numbers in the lake water, as described above, so it might be hard for them to maintain a stable population in the lake water. The faster growth-rate constant of mucus strains in the 20-fold diluted mucus and their insufficient growth in the lake water may result in a characteristic bacterial flora in the mucus which is different from that in the lake water, as revealed in our previous study 6) .…”
Section: Resultsmentioning
confidence: 60%
“…The fish (bluegills, or Lepomis macrochirus) used in this study were sampled as previously reported 6) , at the site (34°58'30'' N, 135°54'30'' E) where the river Seta flows out from Lake Biwa (the largest lake in Japan). The fish were brought back to our laboratory within several hours.…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations